2021
DOI: 10.3847/1538-3881/abdf53
|View full text |Cite
|
Sign up to set email alerts
|

TESS Hunt for Young and Maturing Exoplanets (THYME). V. A Sub-Neptune Transiting a Young Star in a Newly Discovered 250 Myr Association

Abstract: The detection and characterization of young planetary systems offer a direct path to study the processes that shape planet evolution. We report on the discovery of a sub-Neptune-sized planet orbiting the young star HD 110082 (TOI-1098). Transit events we initially detected during TESS Cycle 1 are validated with time-series photometry from Spitzer. High-contrast imaging and high-resolution, optical spectra are also obtained to characterize the stellar host and confirm the planetary nature of the transits. The h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 183 publications
1
67
0
Order By: Relevance
“…In all cases the planet radius shrinks below 3.3 𝑅 ⊕ , and in some cases considerably lower still, in line with evidence that that young planets in open clusters and stellar associations may be larger than their older counterparts (Mann et al 2017;Tofflemire et al 2021). Our results demonstrate that although K2-100b is currently close to or in the Neptunian desert, its position with respect to it could move down towards the boundary or somewhat below it by the time the system reaches an average field age of a few Gyr.…”
Section: K2-100bsupporting
confidence: 84%
See 1 more Smart Citation
“…In all cases the planet radius shrinks below 3.3 𝑅 ⊕ , and in some cases considerably lower still, in line with evidence that that young planets in open clusters and stellar associations may be larger than their older counterparts (Mann et al 2017;Tofflemire et al 2021). Our results demonstrate that although K2-100b is currently close to or in the Neptunian desert, its position with respect to it could move down towards the boundary or somewhat below it by the time the system reaches an average field age of a few Gyr.…”
Section: K2-100bsupporting
confidence: 84%
“…This means the epoch at which features such as the radius-period valley or the Neptunian desert are forged cannot be determined in this way for the foreseeable future, even with the exoplanet discoveries coming out of the TESS mission including some young planets (e.g. Newton et al 2019;Tofflemire et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The TESS mission (Ricker et al 2015) provides a new opportunity for targeted searches of young exoplanets from precise time-series photometry for millions of targets across most of the sky. For example, the THYME survey has identified several planets in known young associations spanning a diversity of Galactic environments, such as the Tucana-Horologium and Ursa Major moving groups (Newton et al 2019;Mann et al 2020), the Scorpius-Centaurus OB association (Rizzuto et al 2020), the Pisces-Eridanus stream (Newton et al 2021), and even a previously unknown association (Tofflemire et al 2021). Other searches of TESS data have revealed planets orbiting young stars in the IC 2602 cluster (Bouma et al 2020) and in the field (Zhou et al 2021).…”
mentioning
confidence: 99%
“…FriendFinder uses the Gaia EDR3 astrometry and radial velocity of a source (we used our IGRINS systemic velocity) to compute Galactic U V W and XY Z, then projects the U V W motion into the tangential velocities et al 2021), the A0 population of the Crux Moving Group (grey squares, Goldman et al 2018), or stars identified using the FriendFinder algorithm restricted to V tan,off < 1km s −1 and within 10 pc of TOI 1227 (blue dots, Tofflemire et al 2021). The planet host, TOI 1227, is marked with a red X, and is in all three lists.…”
Section: The Parent Association Of Toi 1227mentioning
confidence: 99%